RESPON PERTUMBUHAN Tithonia diversifolia TERHADAP INOKULASI CENDAWAN MIKORIZA ARBUSKULA (CMA) - Agustian Agustian; Mutia Faiza; Lusi Maira (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2011)
The success of symbiotic arbuscular mycorrhizal fungi (AMF) in plants was determined by three main factors namely by edaphic factors (environment), genetic and physiological plants and fungi. In this study AMF inoculations were attempted in Tithonia (Tithonia diversifolia) which is known as Mexican sunflower that is often used as a source of green manure. The purpose of this study was to find out AMF species that has the highest physiological compatibility with Tithonia and to study the effects of AMF species on Tithonia growth. Experimental design used in this study was Completely Randomized Design (CRD) with 5 treatments and 3 replications. The data were statistically analyzed the variance, if the value of F-calculated was larger than that of F-table, then the analyses were continued using DNMRT at 5% level of significance. The treatment given were: without AMF, giving inoculant Glomus manihottis, Glomus etunicatum, Gigaspora margarita and a mixture of AMF. The number of spores that are given at each treatment was 100 spores / pot. From this study it could be concluded that Tithonia species could be infected by the inoculated AMF. AMF infection had not yet demonstrated beneficial effects for Tithonia although the frequency of infection and the number of spores on rhizosphere were also high. Inoculation of G., Glomus manihottis, G. etunicatum, and a mixture of AMF did not have a significant influence on plant height, stem and leaf dry weight, fresh and dry weight of roots. Response of Tithonia growth were shown only on the fresh weight of stems and leaves that are found with the inoculation of G. margarita.Keywords: arbuscular mycorrhiza, growth, innoculation, Tithonia diversifolia,